أثر الإبداع الإداري على أداء المورد البشري دراسة حالة عينة من البنوك التجارية بولاية الوادي - شيماء, شافو; نبيلة; جميلة, بوغابة (University of eloued جامعة الوادي, 2020)
"هدفت هذه الدراسة إلى معرفة مدى تأثير الإبداع الإداري على أداء المورد البشري في البنوك محل الدراسة، وكذا مستوى عناصر الإبداع الإداري ( الأصالة ،الحساسية للمشكلات ،المرونة ،القدرة على التحليل ،الطلاقة )، ومدى وجود فروقات ذات دلالة إحصائية على مستوى متغيرات الدراسة تعزى المتغيرات الشخصية . ومن اجل تحقيق أهداف الدراسة اعتمدنا على المنهج الوصفي التحليلي ، لتناسبه مع الإشكالية واستخدمنا الاستبانه كأداة لجمع البيانات في الدراسة الميدانية ،وشملت 34عبارة ،وفي ذلك تم جمع _البيانات وتحليلها واختبار الفرضيات باستخدام الحزم الإحصائية للعلوم الاجتماعية SPSS ، ويتمثل مجتمع الدراسة في بعض الموظفين لخمسة بنوك محل دراسة والبالغ عددهم 60عاملا، ومن خلال استخدام بعض الأساليب الإحصائية المناسبة لفرضيات الدراسة وتساؤلاتها توصلت الدراسة إلى وجود اثر للإبداع الإداري على أداء المورد البشري في البنوك محل الدراسة. ""This study aimed to find out the extent of the influence of administrative creativity on the performance of human resource in the banks under study, The level of administrative creativity (originality, allergies to problems, flexibility, analysis and fluency),The extent to which there are statistically significant differences at the level of study variables are attributable to personal variables. In order to achieve the objectives of the study, we adopted analytical approach, To suit problem and used the questionnaire as a tool for collecting data in the field study, Included 34 words, In that data collected, analyzed and testing of hypotheses using statistical packets of social sciences SPSS, The study community is one of the staff for five banking banks and 60 workers, And through the use of some statistical methds appropriate to the study hypotheses and questions, the study found an impact of administrative creativity on the performance of the human resource in the banks under study. "
مذكرة ماستر ادارة اعمال
Keywords: الإبداع ،الإبداع الإداري ، أداء المورد البشري .البنوك التجارية; Creativity, Administration creativity, Human resources performance. Commercial Banks